The Main Research Directions in the Study of Regional Book Culture: on the Example of the Republic of Buryatia - E. A. Kuchmurukova (Библиосфера, 2023)
In recent years, the number of research on regional book culture has increased. This trend can be traced in Buryatia, where, on the contrary to the consistency of surveys carried on during the Soviet period, they are scattered today. The lack of the holistic idea of the main directions to study Buryatia book culture in different historical periods dictates the need to summarize information on the research carried out, to determine the degree of development of the scientific problem. The purpose of the article is to analyze published sources reflecting various aspects of the development of Buryatia book culture. As a result, a historiographic analysis of scientific works devoted to the history and modern state of book publishing, book distribution, printing industry, republican periodicals was carried out, the research activities of the Department of Library and Information Resources of VSGIK in this direction were described. Summing up the results of many years of work on the study of the topic made it possible to identify gaps and determine the prospects for its further development.